Quantitative genetics of a carotenoid-based color: heritability and persistent natal environmental effects in the great tit. - Evans, SR; Sheldon, B (2012)
The information content of signals such as animal coloration depends on the extent to which variation reflects underlying biological processes. Although animal coloration has received considerable attention, little work has addressed the quantitative genetics of color variation in natural populations. We investigated the quantitative genetics of a carotenoid-based color patch, the ventral plumage of mature great tits (Parus major), in a wild population. Carotenoid-based colors are often suggested to reflect environmental variation in carotenoid availability, but numerous mechanisms could also lead to genetic variation in coloration. Analyses of individuals of known origin showed that, although plumage chromaticity (i.e., color) was moderately heritable, there was no significant heritability to achromaticity (i.e., brightness). We detected multiple long-lasting effects of natal environment, with hatching date and brood size both negatively related to plumage chromaticity at maturity. Our reflectance measures contrasted in their spatiotemporal sensitivity, with plumage chromaticity exhibiting significant spatial variation and achromatic variation exhibiting marked annual variation. Hence, color variation in this species reflects both genetic and environmental influences on different scales. Our analyses demonstrate the context dependence of components of color variation and suggest that color patches may convey multiple aspects of individual state.